Pottery Museum Design Based On Sustainable Tourism In Melikan Village Central Java - Pradityo, Koko; Rukayah, R Siti (Talenta Publisher, 2025)
Melikan Tourism Village is located in Klaten Regency, Central Java Province. This village is known as a center for pottery crafts with a unique technique called the inclined spinning technique, which is estimated to have existed for about 600 years. Despite being known for its pottery crafts, Melikan Village still faces several challenges to ensure the sustainability and development of the village. Based on the historical and cultural background of the village, this study aims to design a pottery museum to address these potentials and challenges. The research employs a qualitative descriptive method, including precedent studies, literature studies, and field surveys. The design of this pottery museum strives to apply the principles of sustainable tourism into its design. The result of this research is a pottery museum design concept that supports aspects of sustainable tourism by integrating economic, socio-cultural, and environmental aspects into a sustainable unity. Keywords: Pottery, Museum, Sustainable Tourism